Continuous Catalyst-Free Esterification of Oleic Acid in Compressed Ethanol. (19th January 2014) - Abdala, Ana Carolina de Araujo; dos Santos Garcia, Vitor Augusto; Trentini, Caroline Portilho; Cardozo Filho, Lúcio; da Silva, Edson Antonio; da Silva, Camila
Abstract : The esterification of oleic acid in a continuous catalyst-free process using compressed ethanol was investigated in the present study. Experiments were performed in a tubular reactor and variables investigated were temperature, pressure, and oleic acid to ethanol molar ratio for different residence time. Results demonstrated that temperature, in the range of 473 K to 573 K, and pressure had a positive effect on fatty acid ethyl esters (FAEE) production. In the experimental range investigated, high conversions can be obtained at low ethanol concentrations in the reaction medium and it was observed that oleic acid to ethanol molar ratios greater than 1 : 6 show no significant increase in conversion. Nonnegligible reaction conversions (>90%) were achieved at 573 K, 20 MPa, oleic acid to ethanol molar ratio of 1 : 6, and 20 minutes of residence time.